The Meaning of Eagles in the Baltic Region. A Case Study from the Castle of the Teutonic Order in Klaipėda, Lithuania (13th–14th Century) - Ehrlich, Freydis; Piličiauskienė, Giedrė; Urbonaitė-Ubė, Miglė; Rannamäe, Eve (Archaeologia Lituana, 2020)
In this paper, we examine archaeological bird remains from Klaipėda Castle (Ger. Memel), western Lithuania. The castle was built in 1252, and during the Middle Ages, it was the northernmost castle of the Teutonic Order in Prussia. The castle together with its adjacent town were subjected to wars and changing political situations over the centuries, but nevertheless represented a socially higher status. The studied bird remains were found during the excavations in 2016 and have been dated by context to the Middle Ages – from the end of the 13th to the beginning of the 14th century. Our aim is to introduce and discuss the bird remains with an emphasis on two species – the white-tailed sea-eagle (Haliaeetus albicilla) and golden eagle (Aquila chrysaetos). Most of all, we are interested in their role in expressing people’s social status, use in material culture, and significance as a food source. Our analysis showed that in Klaipėda, the eagles were probably used for raw material and possibly for feathers, but not for hawking and food. Alternatively, they could have been killed for scavenging. Other species identified in the assemblage such as chicken (Gallus gallus domesticus), grey partridge (Perdix perdix), geese (Anser sp.), ducks (Anatinae), and great cormorant (Phalacrocorax carbo) were mainly interpreted as food waste. This article presents the first concentrated study on bird remains from Klaipėda and is one of the first discussions about the meaning of eagles in the Baltic region.